Development of anti-obesity herbal drink from butterfly pea flower (Clitoria ternatea) extract and lemon (Citrus limon) juice - AGUSTIARINI DEWI ANUGRAHANI; DONO INDARTO; ETI PONCORINI PAMUNGKASARI; LILIK WIJAYANTI; FISTA UTAMI (Smujo International, 2025)
Abstract. Anugrahani AD, Indarto D, Pamungkasari EP, Wijayanti L, Utami F. 2025. Development of anti-obesity herbal drink from butterfly pea flower (Clitoria ternatea) extract and lemon (Citrus limon) juice. Nusantara Bioscience 17: 129-136. Obesity is a multifactorial disease with a high global prevalence and higher risk for cardiometabolic diseases. Obesity management comprises diet, physical exercise, and pharmacotherapy. Some obese patients have low compliance with diet and exercise therapy, while long-term use of anti-obesity drugs causes adverse side effects. Herbal drinks have also been used for obesity treatment, but their efficacy remains debatable. Herbal drink products have been developed, including butterfly pea flower extract and lemon juice, which contain flavonoids and anthocyanins that have anti-obesity activity. The purpose of this study was to create a herbal drink for obesity treatment and analyze acceptability, microbiological contamination, and nutritional and phytochemical contents. An organoleptic test assessed the acceptability of the herbal drink. Analysis of macronutrient content used proximate methods. Vitamin C and microbiological tests were performed using spectrophotometric and Total Plate Count (TPC) methods. Delphinidin and hesperidin levels were measured using a High-Performance Liquid Chromatography (HPLC) method. Statistical analysis was performed using Kruskal-Wallis and followed by the post-hoc Mann-Whitney with p<0.05 to determine the best formula of the four formulas (F1-F4) in this study. Organoleptic test results showed that formulation F3 of the herbal drink was the most liked and acceptable by the panelists. The herbal drink (F3) contained 0.82% fat, 0.34% protein, 0.099% carbohydrate, 3,527.25 mg/100 g vitamin C, 21.66 ppm delphinidin, and 525.68 ppm hesperidin. In conclusion, herbal drink has the potential to become an alternative anti-obesity treatment. Further research is needed to test the effectiveness of herbal drinks on weight loss and lipid profile improvement in obese patients.